Raggedy Ann stories - Gruelle, Johnny (1880-1938) (Washington, D.C. : Office of English Language Programs, 2011)
Raggedy Ann Stories contains 13 stories about a rag doll named Raggedy Ann and her friends. In these stores, Raggedy Ann shares many exciting adventures with her doll friends. Sometimes they get themselves into trouble, and many times they help others. Through these stories,they learn to listen, forgive others when they make a mistake, and to be nice to people around them. Raggedy Ann stories is a classic American children's book; this version has been abridged and revised for English Language learners. This book uses vocabulary at the first 1,000 word level. Words above this level are in bold type type and are explained in the Glossary at the back of the book.
Table of Contents agged Ann Character List 1. Introduction 2. Raggedy Ann Learns a Lesson 3. Raggedy Ann and the Washing 4. Raggedy Ann and the kite 5. Raggedy Ann and the Painter 6. Raggedy Ann saved fido 7. Raggedy Ann's trip on the river 8. Raggedy Ann and the new dolls 9. Raggedy Ann and the cats 10. Raggedy Ann and the gift 11. Raggedy Ann and the chickens 12. Raggedy Ann and the mouse 13. Raggedy Ann and the new sister Vocabulary Glossary by story
Incluye Table of Contents
Incluye Vocabulary Glossary by Story
Keywords: NORTH AMERICAN LITERATURE -- SHORT STORIES; SHORT STORIES